Analisis Kepatuhan Wajib Pajak dalam Pelaporan dan Pembayaran Pajak Penghasilan (PPh) di Indonesia - Catherine Valencia Lee; Jennice; Eilen Luskie; Novita Angel Yang; Shelina (Jurnal Riset Bisnis dan Ekonomi Digital, 2025)
Tax compliance is essential to ensure an effective tax system and encourage economic growth. Taxpayer compliance is influenced by an understanding of tax obligations, effective supervision, and external factors such as tax awareness. This study looks at how corporate and personal tax compliance with the submission of annual tax returns has an impact on increasing corporate and personal income tax revenues. This study uses the literature review method